Theoretical and methodological bases of formation of the professional-pedagogical culture of the future elementary school teacher - Онищенко, І. В. (Pedagogy of Higher and Secondary Education, 2012)
I. V. Onyshchenko.Theoretical and methodological bases of formation of the professional-pedagogical culture of the future elementary school teacher. The article explains the purpose of vocational and educational culture of primary school teacher, its structure, established psychological and pedagogical conditions and stages of formation technology professional and pedagogical culture of the future primary school teacher.